Different Eukaryotic Initiation Factor 2Bε Mutations Lead to Various Degrees of Intolerance to the Stress of Endoplasmic Reticulum in Oligodendrocytes - Na Chen; Yu-Wu Jiang; Hong-Jun Hao; Ting-Ting Ban; Kai Gao; Zhong-Bin Zhang; Jing-Min Wang; Ye Wu (Chinese Medical Journal, 2015)
Background: Vanishing white matter disease (VWM), a human autosomal recessive inherited leukoencephalopathy, is due to mutations in eukaryotic initiation factor 2B (eIF2B). eIF2B is responsible for the initiation of protein synthesis by its guanine nucleotide exchange factor (GEF) activity. Mutations of eIF2B impair GEF activity at different degree. Previous studies implied improperly activated unfolded protein response (UPR) and endoplasmic reticulum stress (ERS) participated in the pathogenesis of VWM. Autophagy relieves endoplasmic reticulum load by eliminating the unfolded protein. It is still unknown the effects of genotypes on the pathogenesis. In this work, UPR and autophagy flux were analyzed with different mutational types. Methods: ERS tolerance, reflected by apoptosis and cell viability, was detected in human oligodendrocyte cell line transfected with the wild type, or different mutations of p. Arg113His, p. Arg269FNx01 or p. Ser610-Asp613del in eIF2Bε. A representative UPR-PERK component of activating transcription factor 4 (ATF4) was measured under the basal condition and ERS induction. Autophagy was analyzed the flux in the presence of lysosomal inhibitors. Results: The degree of ERS tolerance varied in different genotypes. The truncated or deletion mutant showed prominent apoptosis cell viability declination after ERS induction. The most seriously damaged GEF activity of p. Arg269FNx01 group underwent spontaneous apoptosis. The truncated or deletion mutant showed elevated ATF4 under basal as well as ERS condition. Decreased expression of LC3-I and LC3-II in the mutants reflected an impaired autophagy flux, which was more obvious in the truncated or deletion mutants after ERS induction. Conclusions: GEF activities in different genotypes could influence the cell ERS tolerance as well as compensatory pathways of UPR and autophagy. Oligodendrocytes with truncated or deletion mutants showed less tolerable to ERS.